Views and experiences of using integrated care pathways (ICPs) for caring for people in the last days to hours of life: results from a cross-sectional survey of UK professionals. Issue 3 (6th January 2015) - Collins, K A; Hughes, P M; Ibbotson, R; Foy, G; Brooks, D
Abstract : Objectives: To determine the views and experiences of health and social care professionals on using integrated care pathways (ICPs)for caring for people in the last days to hours of life. Methods: Online cross-sectional questionnaire survey of UK professionals working in UK primary and secondary care settings. Results: 1331 professionals returned completed questionnaires. Ninety-three per cent (1138/1228) of respondents used the Liverpool Care Pathway (LCP) or local variant. Eighty-eight (1089/1234) felt ICPs enabled professionals to provide better care for individuals and their families/carers. ICPs were viewed as promoting patient-centred holistic care, improving pain and symptom control, providing guidance and standards and improving communication with patients/families. Sixty-two per cent (770/1234) had no concerns regarding the use of ICPs. Areas of concern included incorrect use and implementation of the ICP, poor communication with families, junior level staff making decisions and insufficient education and support. Conclusions: There was strong support for using ICPs for caring for people in the last days to hours of life. ICPs were viewed as supporting high-quality patient-centred holistic care. Given the recommendations of the More Care Less Pathway report, those that develop the guidance and support that replace the LCP need to incorporate the aspects of this that have resulted in the benefits seen by professionals within this survey, but also learn from the instances where ICPs have failed to prevent poor care, or worse, have contributed to it.